BIOCHEMICAL CHARACTERISTICS OF THE FORMATION OF THE PIGLETS OF THE FIRST DAY OF LIFE - Панікар, І. І. (Scientific Progress & Innovations, 2013)
The level of many indicators of clinical metabolism, especially protein fractions in the blood serum of piglets in the «pre-colostrum» period significantly differ from that of the piglets of the first day of life fed by colostrum. Changing the parameters of protein metabolism is associated with intake of colostrum proteins. Increase of ALT, LDH levels of glucose, serum total bilirubin with a decrease of alkaline phosphatase and urea in the blood indicates a stressful condition of the body, which can be explained by a stress factor, obtained by the body during and immediately after birth.